Pengaruh Penjualan, Current Ratio (CR), Debt to Equity Ratio (DER) dan Gross Profit Margin (GPM) Terhadap Harga Saham (Studi Kasus pada PT. Modern Internasional, Tbk. Periode Tahun 2009-2018) - Pebriani, Hilda; Buchory, Herry Achmad (STIE Ekuitas, 2020)
Purpose of this research is to examine the impact Sales, Current Ratio (CR), Debt to Equity Ratio (DER) and Gross Profit Margin (GPM) on Stock Price (Case Study at PT. Modern Internasional, Tbk. Period 2009-2018). The method of the research are descriptive and verification method, and used secondary data sourced from Published Financial Report Period 2009-2018. Data analysis technique that used are statistic descriptive test, classical assumption test, multiple linier regression, coefficient correlation, coefficient determination, t statistic test and f statistic test. The result of this research showed that partially Sales, has not effect on stock price. Current Ratio (CR) has effect and significant on stock price. Debt to Equity Ratio (DER) has not effect on stock price. Gross Profit Margin (GPM) has effect and significant on stock price. The magnitude of influence by 74,8% while the remaining 25,2% is influenced by other factors not tested in this study. Keywords: Sales, Current Ratio, Debt to Equity Ratio, Gross Profit Margin, Stock Price, Modern Internasional.